Frequency of G6PD (Glucose 6-Phosphate Deficiency) Anemia in the Patients Attending Peoples University Hospital Nawabshah. - Naveed sattar shaikh1, shaiza jamali2, ameer ali jamali3, (Journal of Peoples University of Medical & Health Sciences Nawabshah. (JPUMHS), 2019)
Objective: To find out the frequency of glucose 6-phosphate deficiency anemia in the patients attending peoples university hospital Nawabshah. Materials and Method: Type of study: Retrospective study. Sample size: 456. Duration of study: September 2017 to August 2019. Place of study: Nawabshah Sindh Pakistan. Sample collection and processing: Patient 5.0 mL blood samples were collected by venipuncture in an EDTA tube. To screen for G6PD deficiency using a fluorescence test, and using UDi G6P-DH kit from (United Diagnostics, Langenhagen, Germany) the anticoagulated whole blood was used. 5µl of anticoagulated whole blood was added directly into 100µl of working reagent, then mixed and incubated at room temperature for 10 minutes. After incubation, placed 10µl of resulting solution on the provided filter paper and waited to dry (15 minutes at 37°C) in a dark room, viewed the filter paper under a long wave UV light. Samples with normal or slightly deficient G6PD activity was shown fluorescence, while no fluorescence suggested complete lack or marked deficiency of G6PD. Results: Total 456 patients were recruited from 1088. Out of them 203 were males and 253 were females. 35 females (13.83%) were positive for G6PD out of 253 while 218 (86.16%) were negative. 59 males (29.06%) were positive for G6PD out of 203 while 144 (70.93) were negative. Conclusion: This research study found that G6PD deficiency is not so prevalent in the Nawabshah and its peripheries because only 20.61% showed positive results may be due to short duration of study as well as sample size.